2016
DOI: 10.1136/bcr-2016-215440
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of hereditary multiple exostoses presenting with compressive myelopathy

Abstract: A 15-year-old boy presented with progressive weakness of both lower limbs. He had classical clinical features suggestive of multiple hereditary exostoses (MHE). Imaging studies of the spine revealed osteochondromas at D7, D11 and L5 vertebrae. The tumour at D11 was encroaching into the spinal canal and causing cord compression. The patient underwent osteochondroma excision and posterior spinal stabilisation, following which there was complete neurological recovery by 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Lesions of the vertebral column are more common in the superior spine; 30-80% of the lesions have been reported in the cervical spine, 20-30% in the thoracic spine and only a few reports have cases in the lumbar region [29]. Specially C2 is the most common vertebra to have a tumour followed by C3 and C6 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions of the vertebral column are more common in the superior spine; 30-80% of the lesions have been reported in the cervical spine, 20-30% in the thoracic spine and only a few reports have cases in the lumbar region [29]. Specially C2 is the most common vertebra to have a tumour followed by C3 and C6 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Specially C2 is the most common vertebra to have a tumour followed by C3 and C6 [27]. Jackson et al [28] reported that the average lesions in a single patient was 2.25 with the range being between 1 and 4, in addition it has been stated that finding lesions in multiple levels of the vertebral column is rare [29]. The osteochondromas that do grow on the vertebrae can occur in multiple areas reflecting the many ossifications centres; they are found on the vertebral bodies, tips of the spinous processes, the transverse processes and the articular processes [5].…”
Section: Discussionmentioning
confidence: 99%